HISTOPATHOLOGICAL CHARACTERISTICS OF GASTRIC CARCINOMA AND ITS RELATION WITH ABO BLOOD GROUP IN KURDISH PEOPLE - Daood, Rawaz Salah; Salaye, Jangy Shawkat (Journal of Sulaimani Medical College, 2018)
Background Many studies have been done of relationship between blood group and cancers. Objectives To evaluate the relationship between ABO blood group system and the risk of gastric cancer with its histopathological features among Kurdish population by case-control study. Materials and Methods In our retrospective case-control study, 194 cases of gastric cancer were enrolled from March 2013 to October 2017 The patients were of Kurdish ethnicity, data on age, sex, hisopathological result, blood group, grade and stage at diagnosis were collected, association with ABO blood group and gastric cancer were assessed. Results This study showed that blood group A might be a risk factor of gastric cancer in both males and females. The intestinal type adenocarcinomas were the most frequent hisopathological subtype of gastric carcinoma among blood group A. Grade 3 of differentiation found to be most frequent in blood group A patients (20.1%). Conclusion Individuals with blood group A has a higher risk of developing gastric cancer in their lifetime and their disease would be of high grade which might predict poor prognosis, while people with blood group AB have the lowest risk of developing gastric cancer.
Keywords: Gastric cancer; Blood group; Kurdish population